PENGGUNAAN KONJUNGSI DALAM WACANA KRIMINAL KOLOM BORGOL DI SURAT KABAR RAKYAT BENGKULU EDISI NOVEMBER—DESEMBER 2016 - Tri Dina Ariyanti; Iming Fentaria (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2017)
Abstract. Commonly used in a variety of language news reports hearts: journals, electronic media (TV, radio) and print media (magazines, newspapers). Language presents news Facts Operates Whole And Objective. Media Under The written language used variety is characterized WITH accuracy using the Spelling and punctuation (CAN symbolizes Right Operative intonation), vocabulary, grammar USE hearts of word formation, formulation of sentences, paragraphs, and Discourse. Variety Singer stressed USE standard variety, Spelling (EYD) The raw, raw Yang vocabulary, form of the word berimbuhan, And The Complete Operating grammatical sentence. Thus Article Search Google, hearts using conjunctions also Also CAN WITH Good note that preparation was clear sentences and paragraphs Being. Conjunction serves to review the sentence linking Parts OR sentence Which One other sentence hearts WITH A Discourse. Objective, ie to get description review USE Conjunction Errors hearts Discourse Crime Handcuffs column in People's Daily Newspaper Bengkulu --23 December edition of 23 November 2016. The method used is descriptive Singer Research hearts. Singer Research hearts descriptive method is used to get the description of USE conjunctions review hearts Column handcuffs criminal discourse in Bengkulu People's Daily Newspaper. Forms USE Conjunction Coordinating IN Daily Newspapers Rakyat Bengkulu: based on analysis of the data shows that the USE conjunction coordinative which was used in the newspaper People's Daily Bengkulu IN Discourse criminal Column handcuffs From 23 As of November December 23, 2016 the use of conjunctions: And, And, OR, but, but, but, meanwhile. Forms USE IN correlative conjunctions People's Daily Newspaper Bengkulu: correlative conjunctions are not found Discourse hearts column criminal handcuffs ON newspaper People's Daily Bengkulu From 23 December 23, 2016. As of November forms of subordinating conjunctions USE IN Peoples Daily Newspaper Bengkulu: conjunctions suborinatif consisting Of Three twelve KIND, based on analysis of data on differences, conjunctions used hearts newspaper People's daily Bengkulu From 23 November until December 23, 2016 are: (1) Relationship time: since when, wHILE, Serta, taxable income, BEFORE, Up, (2) Relationship Requirements: IF, If (3) Relationship supposition: can not be found, (4) Relationship goal: to be, (5) Relationship konsesif: although, (6) Relationship of comparison: as, as, as (7) The relationship causes : causes, bECAUSE (8) Relationship findings: thus, Up, so, (9) Relationship tool: BY, Without, (10) Relationship Method: BY, Without, (11) Relationship complementation: b ahwa, (12) Relationship attributive: Yang (13) Relationship COMPARISON: not found. Conjunction shape Antarkalimat USE IN Peoples Daily Newspaper Bengkulu: conjunctions between sentences singer found its use are: then, taxable income, then, in addition to, in fact, but, but. Keywords: Conjunction, Newspapers